2015
DOI: 10.1155/2015/134708
|View full text |Cite
|
Sign up to set email alerts
|

New Developments in Peritoneal Fibroblast Biology: Implications for Inflammation and Fibrosis in Peritoneal Dialysis

Abstract: Uraemia and long-term peritoneal dialysis (PD) can lead to fibrotic thickening of the peritoneal membrane, which may limit its dialytic function. Peritoneal fibrosis is associated with the appearance of myofibroblasts and expansion of extracellular matrix. The extent of contribution of resident peritoneal fibroblasts to these changes is a matter of debate. Recent studies point to a significant heterogeneity and complexity of the peritoneal fibroblast population. Here, we review recent developments in peritonea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 69 publications
1
26
0
2
Order By: Relevance
“…31 Moreover, fibroblast play a role in this process. 32 As a result the peritoneal membrane undergoes a progressive remodeling with the accumulation of extracellular matrix and fibrosis. Peritoneal infections aggravate the peritoneal membrane remodeling process.…”
Section: Biomarker Research In the Context Of Chronic Peritoneal Inflmentioning
confidence: 99%
“…31 Moreover, fibroblast play a role in this process. 32 As a result the peritoneal membrane undergoes a progressive remodeling with the accumulation of extracellular matrix and fibrosis. Peritoneal infections aggravate the peritoneal membrane remodeling process.…”
Section: Biomarker Research In the Context Of Chronic Peritoneal Inflmentioning
confidence: 99%
“…In PD, the peritoneum is used as a semipermeable membrane to remove metabolic wastes and excess water in the body according to dispersion and penetration principles [2,3]. It has always been thought that the activation of fibroblasts inherent in peritoneal tissue and the infiltration of inflammatory cells are the most important factors that cause structural and functional changes in peritoneal tissue [16]. However, recent studies have found that the long-term stimulation by nonbiocompatible peritoneal dialysis solution can lead to the EMT of peritoneal mesothelial cells [2,3,16].…”
Section: Discussionmentioning
confidence: 99%
“…It has always been thought that the activation of fibroblasts inherent in peritoneal tissue and the infiltration of inflammatory cells are the most important factors that cause structural and functional changes in peritoneal tissue [16]. However, recent studies have found that the long-term stimulation by nonbiocompatible peritoneal dialysis solution can lead to the EMT of peritoneal mesothelial cells [2,3,16]. EMT is a highly regulated process that has a vital role in embryonic development, tumor formation and fibrosis in some chronic inflammatory diseases [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Кілька попередніх досліджень, зосереджені на кореляції між вмістом у ексфузаті прозапальних цитокінів та швидкістю перитонеального транспорту, продемонстрували негативний вплив хронічного місцевого запалення на функцію перитонеуму [7,8,19]. Тим не менш, локальна продукція про-та проти-фіброгенних медіаторів, а також їх вплив на функцію очеревини і адекватність перитонеального діалізу залишається не визначеною.…”
Section: №4 (52) 2016unclassified